Optimal abdominal CT protocol for obese patients. Issue 1 (February 2018) - Qurashi, A.; Rainford, L.; Ajlan, A.; Khashoggi, K.; Ashkar, L.; Al-Raddadi, M.; Al-Ghamdi, M.; Al-Thobaiti, M.; Foley, S.
Abstract: Introduction: This study investigated the impact of different protocols on radiation dose and image quality for obese patients undergoing abdominal CT examinations. Methods: Five abdominal/pelvis CT protocols employed across three scanners from a single manufacturer in a single centre used a variety of parameters (kV: 100/120, reference mAs: 150/190/218/250/300, image reconstruction: filtered back projection (FBP)/iterative (IR)). The routine protocol employed 300 reference mAs and 120 kV. Data sets resulting from obese patient examinations ( n = 42) were assessed for image quality using visual grading analysis by three experienced radiologists. Objective assessment (noise, signal/contrast-noise ratios) and radiation dose was compared to determine optimal protocols for prospective testing on a further sample of patients ( n = 47) for scanners using FBP and IR techniques. Results: Compared to the routine protocol, mean radiation dose was reduced by 60% when using 100 kV and SAFIRE technique strength 3 ( p = 0.001). Reduction of up to 30% in radiation dose was noted for the FBP protocol: 120 kV and 190 reference mAs ( p = 0.008). Subjective and objective image quality for both protocols were comparable to that of the routine protocol ( p > 0.05). An overall improvement in image quality with increasing strength of SAFIRE was noted. Upon clinical implementation of the optimal dose protocols, local radiology consensus deemed image quality to be acceptable for the participating obese patient cohort. Conclusion: Radiation dose for obese patients can be optimised whilst maintaining image quality. Where iterative reconstruction is available relatively low kV and quality reference mAs are also viable for imaging obese patients at 30–60% lower radiation doses. Highlights: Iterative reconstruction allows the use of 100 kV for scanning obese patients. Lower kV settings allows substantial radiation dose saving with similar image quality. Lower mAs can provide an opportunity to optimise the CT scans of obese patients due to the greater natural tissue contrast.